Marine sponges in the once and future ocean. (3rd January 2022) - Mills, Daniel B.; Sperling, Erik A.
Abstract : Animals originated under hypoxia—low‐oxygen conditions that are currently expanding throughout the global ocean. How marine sponges respond to hypoxia is both relevant to reconstructing early animal evolution and for forecasting the fate of modern marine ecosystems. In a new effort, multiple sponge species from two different oceans were found to tolerate hypoxia in the lab, revealing a more general capacity for hypoxia tolerance across sponges with implications for both the deep past and near future of animal life.